The Developing Child / Ninth Edition - Bee Helen (Allyn And Bacon, 2000)
This book allows students to understand how theory and research are interconnected and how they apply to everyday life. Introduction, Basic Questions, The Beginnings of Life, Prenatal Development, Birth and the Newborn Child, The Physical Child, Physical Development, Perceptual Development, The Thinking Child, Cognitive Development I: Structure and Process, Cognitive Development II: Individual Difference in Cognitive Abilities, The Development of Language, The Social Child, Personality Development: Alternative Views, The Concept of Self in Children, The Development of Social Relationships, Thinking About Relationships: The Development of Social Cognition, The Whole Child, The Ecology of Development: The Child Within the Family System, Beyond the Family: The Impact of the Broader Culture, Atypical Development, Putting It All Together: The Developing Child, Glossary, References, Name and Subject Index.